2010
DOI: 10.1007/s10708-010-9389-z
|View full text |Cite
|
Sign up to set email alerts
|

“My garden is a great help”: gender and urban gardening in Buea, Cameroon

Abstract: At a time of economic crisis and sharply rising food prices, urban farming is increasingly helping to sustain households. Gender is generally thought to be a key variable in this but studies are still in their infancy. Looking at the phenomenon from a livelihood perspective and based on a survey carried out in Buea, Cameroon, this paper deals with a number of key issues related to gender and urban gardening, including access to resources, division of labour and the benefits and challenges encountered. An addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 31 publications
2
23
1
Order By: Relevance
“…The gendered difference observed in the cropping systems may be due to differences in access to land. In fact, men had larger plot sizes compared to women, as it was also reported in vegetable production systems in Buea, Cameroon [26] and in southwestern Nigeria [30]. This supports the general gender-differentiated resource base of African farming systems [29,31].…”
Section: Gender Vegetable Farming Systems and Diversity Of Vegetablesupporting
confidence: 77%
See 2 more Smart Citations
“…The gendered difference observed in the cropping systems may be due to differences in access to land. In fact, men had larger plot sizes compared to women, as it was also reported in vegetable production systems in Buea, Cameroon [26] and in southwestern Nigeria [30]. This supports the general gender-differentiated resource base of African farming systems [29,31].…”
Section: Gender Vegetable Farming Systems and Diversity Of Vegetablesupporting
confidence: 77%
“…Vegetable species are dominated by African indigenous species, and the use of improved seeds is low. It is a part-time activity for the majority of people involved and represents a typical example of traditional vegetable farming systems common in West Africa [26]. Indeed, in traditional vegetable farming systems, vegetable production and marketing are undertaken mainly by women [2,26,27].…”
Section: Gender Vegetable Farming Systems and Diversity Of Vegetablementioning
confidence: 99%
See 1 more Smart Citation
“…As for the latter, this high percentage is related to the fact that cattle -which require thorough care -are very commonly held. A recent study among urban gardeners in Buea, Cameroon (Ngome and Foeken 2012) found that more than 40% of the farmers considered lack of education and training as a constraint. This applied more to female gardeners (61%) than male gardeners (21%).…”
Section: Provide Support and Educationmentioning
confidence: 99%
“…Usually, women were involved in these transactions on the producers" side and obviously only small quantities were traded this way. Yet, some urban farmers were not satisfied with the marketing infrastructure, as these remarks -all from Mbeya -illustrate: In the earlier mentioned Buea (Cameroon) study (Ngome and Foeken, 2012), despite the fact that the research locations enjoyed good road networks and are strategically located near two major markets to allow for the easy transportation of vegetables (mainly tomatoes) to sell, some respondents still complained about "market constraints". Moreover, in order to improve the situation, many gardeners suggested the provision of cooled, public storage facilities so that post-harvest losses could be reduced.…”
Section: Improving Market Conditionsmentioning
confidence: 99%